Feeding practices and growth of preterm infants discharged from the Neonatal Intensive Care Unit at Auckland City Hospital until twelve months corrected age : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - Vitali, Jennifer Angela-Jane (Massey University, 2014)
Background: Preterm infants are unique in their physiological, developmental and nutritional needs. Previous research regarding the preterm infant has focused on interventions within the hospital setting. Recently the lack of research in the post discharge period has been highlighted. The period after discharge poses a vulnerable period as previous intensive care, growth and nutritional monitoring of the infant are no longer readily available. The aim of this study was to identify current breastfeeding, complementary feeding, feeding practices and growth of preterm infants after hospital discharge from the Neonatal Intensive Care Unit (NICU) at Auckland City Hospital until twelve months corrected age. Method: Infants who were born preterm (<37 weeks’ gestation) were recruited from Auckland City Hospital NICU, a tertiary care level hospital. Homes visits were undertaken at four months after discharge and at twelve months corrected age to collect anthropometric measurements. Online surveys were administered at four months post discharge and at six, nine and twelve months corrected age. Data collected included demographic information at birth, mode of feeding, age of introduction of complementary foods and types of foods introduced to infants. Data were analysed using descriptive statistics. Group comparisons were made using Pearson’s chi-square (2), Fishers Exact test and paired T- tests. Differences were considered significant at P< 0.05. Results: Sixty-eight preterm infants were recruited from the NICU at Auckland City Hospital of whom the majority (76%) were born moderate to late preterm. The median (range) age of babies was 34 weeks (24+2 - 36+6 weeks) and their mean (± SD) birth weight was 2.03 ± 0.65 kg. At hospital discharge 73% of the infants were exclusively breastfed. By four months after discharge this had decreased to 46%, and by 12 months corrected age, only 21% of babies continued to be breastfed. The mean chronological age of complementary food introduction was 23 ± 4.4 weeks (range 12 - 34 weeks). The majority of the babies (84%) started complementary feeding within the recommended age range. The most common first food was baby rice (45%) and infants showed increasing variation in their diet from six until twelve months corrected age. Z-scores for weight, length and head circumference were calculated using UK-WHO data. There was a significant decrease in mean Z-scores for weight, length and head circumference between birth and hospital discharge. The majority of infants regained this deficit by four months and twelve months corrected age. Although, there were a few infants found to be at risk of growth faltering. Conclusion: This study shows that the majority of preterm infants discharged from the NICU are breastfed at discharge, although, breastfeeding declines significantly by four months after discharge and thereafter. The majority of infants are introduced to complementary feeding appropriately although the choices of early complementary foods need to be addressed to include high energy nutrient dense foods. Lastly, growth in the post discharge period of these infants was adequate to support and maintain growth for the majority of infants, more research is needed to determine the feeding practices over this time which impacted on growth.
Keywords: Premature infants; Nutrition; Hospital care; Auckland; New Zealand; Neonatal Intensive Care Unit